Implementation Of The Strengthening Character Education Policy In Elementary Schools and Madrasah Ibtidiyah - Rohman, Rohman; Mentari, Ana (Universitas Tanjungpura, 2024)
The Strengthening Character Education Policy has been implemented in schools since the enactment of Permendikbud Number 20 of 2018 concerning Strengthening Character Education in Formal Education Units which is a continuation of previous character education known as National Character Culture. The process of implementing Strengthening Character Education in schools has not been evaluated so far. The long-term goal of this research is that the implementation of the strengthening of character education policy at the primary and MI levels runs effectively in accordance with the expected goals. The specific targets to be achieved are to obtain an overview of: 1) Context in the implementation of PPK policy, 2) Input in the implementation of PPK policy, 3) Process in the implementation of PPK policy, 4) Product in policy implementation, 5) inhibiting factors and supporting factors in the implementation of PPK policy for each component or dimension of the policy at elementary and MI in Bandar Lampung City, 6) comparison of the implementation of PPK policy implemented in elementary and MI in Bandar Lampung City refers to the components or dimensions of the policy as well as inhibiting and supporting factors in policy implementation, and 7) produce recommendations for the implementation of PPK in Elementary Schools (SD) and MI in Bandar Lampung City. Translated with DeepL.com (free version). The data collection techniques used were interviews, observation and documentation. Data analysis techniques include data collection, data reduction, data presentation and conclusion drawing. The results showed that there has been an implementation of the five PPK values in elementary schools in Bandar Lampung city. Among them, the implementation of religious values through routine duha prayer activities in congregation every Saturday. Implementation of nationalist values through flag ceremony activities every Monday and other national day commemorations. Implementation of the value of mutual cooperation through Clean Friday activities in the school environment. Implementation of integrity values through honesty to students, and implementation of independent values by getting used to taking exams without cheating. The implementation of the five PPK values is carried out through habituation and exemplary behavior from teachers.